2011
DOI: 10.1111/j.1447-0349.2010.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the ‘right patient’: Nurse and consumer perspectives on verifying patient identity during medication administration

Abstract: Accurate verification of patient identity during medication administration is an important component of medication administration practice. In medical and surgical inpatient settings, the use of identification aids, such as wristbands, is common. In many psychiatric inpatient units in Victoria, Australia, however, standardized identification aids are not used. The present paper outlines the findings of a qualitative research project that employed focus groups to examine mental health nurse and mental health co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
(8 reference statements)
0
9
0
6
Order By: Relevance
“…Mental health units must endeavour to improve the process for patient identification using wristband identification and interpersonal engagement (Kelly et al . ). Currently, wristbands are not routinely used within the unit under study, despite the endorsement from ACSQHC, a supporting hospital policy and recent education undertaken to challenge the existing workplace culture.…”
Section: Discussionmentioning
confidence: 97%
“…Mental health units must endeavour to improve the process for patient identification using wristband identification and interpersonal engagement (Kelly et al . ). Currently, wristbands are not routinely used within the unit under study, despite the endorsement from ACSQHC, a supporting hospital policy and recent education undertaken to challenge the existing workplace culture.…”
Section: Discussionmentioning
confidence: 97%
“…Many hospitals have introduced wristbands as a means to control patients’ identity, including the psychiatric hospital where our study was carried out. In a study of how and whether nurses identify patients in a psychiatric hospital setting, it was found that the use of wristbands was erratic and influenced by a psychiatric nursing culture rooted in the belief that (good) nurses know who the patients are 22. The inconsistency in using the patient’s wristband for identification has also been addressed in somatic settings, and it has been shown in simulation tests that as many as 61% of nurses do not discover an unexpected identity error 23,24.…”
Section: Discussionmentioning
confidence: 99%
“…Students may have confirmed patient identity before the first procedure, and therefore thought it unnecessary to confirm identity again before inserting the peripheral venous catheter. To be able to make a correct assessment here, students need to be informed of the importance of accurate patient identification prior to each procedure (36).…”
Section: Discussionmentioning
confidence: 99%